Comparison of Different Concentrations of Ropivacaine Used for Ultrasound-Guided Adductor Canal Block + IPACK Block in Total Knee Arthroplasty - Wang, Qiuru; Hu, Jian; Ma, Ting; Zhao, Dongmei; Yang, Jing; Kang, Pengde (The Journal of Knee Surgery, 2022)
This study aimed to compare the analgesic efficacy of different concentrations of ropivacaine used for the combination of ultrasound-guided adductor canal block (ACB) and infiltration between the popliteal artery and capsule of the posterior knee (IPACK) block in total knee arthroplasty (TKA). Before general anesthesia, 90 patients undergoing TKA were randomized to receive ACB + IPACK block with ropivacaine 0.2, 0.25, or 0.3% (defined as group A, B, and C, respectively). Primary outcome was the reported visual analog scale (VAS) pain scores at rest 30 minutes following arrival to the postanesthesia care unit (PACU). Secondary outcomes were postoperative VAS pain scores, postoperative morphine consumption, the time to first rescue analgesia, functional recovery of knee (including the range of motion and quadriceps strength), and postoperative complications. Compared with group A, group B and group C had significantly lower VAS scores 30 minutes following arrival to the PACU (p < 0.001 and p < 0.001, respectively). These two groups also had significantly lower VAS pain scores at postoperative 2 hours (at rest: p = 0.037 and 0.002; during motion: p = 0.035 and 0.001, respectively) and 6 hour (at rest: p = 0.033 and 0.002; during motion: p < 0.001 and p < 0.001, respectively), lower postoperative morphine consumption (p = 0.001 and 0.002, respectively), longer time to first rescue analgesia (p = 0.010 and 0.009, respectively), and better range of knee motion on the day of surgery (p = 0.008 and 0.002, respectively). Group B and group C showed no significant differences in these outcomes between each other (p > 0.05). The three groups did not show a significant difference in postoperative quadriceps strength and complication rates (p > 0.05). Compared with ropivacaine 0.2%, ropivacaine 0.25 and 0.3% can provide early pain relief in the first 6 hours after surgery. Ropivacaine 0.25 and 0.3% may provide more clinical benefits for patients undergoing outpatient TKA.
Keywords: total knee arthroplasty; adductor canal block; IPACK; ropivacaine; concentration